Carbon Nanotubes on Highly Interconnected Carbonized Cotton for Flexible and Light‐Weight Energy Storage. (2nd May 2017) - Rana, Masud; Asim, Sumreen; Hao, Bin; Yang, Sudong; Ma, Peng‐Cheng
Abstract : Development of novel light‐weight materials with high areal/volumetric energy density using bioresources provides a sustainable solution for portable energy storage devices. Most of the existing materials are powders or disordered textures with marginal interconnectivity among micro‐/mesoporous structures, leading to a low specific capacitance per geometric area and higher internal resistance as electrode materials. This work describes a simple strategy to develop carbon nanotubes on highly interconnected fibers in a carbonized cotton cloth using a single‐step chemical vapor deposition method. The developed material shows hierarchical structures with low weight (0.27 g cm −3 ), high surface area (137 m 2 g −1 ), and excellent electrical conductivity (3.0 S cm −1 ). When employing the developed material as electrodes for aqueous and solid–gel electrolyte based supercapacitors, the sample exhibits specific areal capacitances of 1286 mF cm −2 (at 1 mA cm −2 current density) and 1140 mF cm −2 (at 2.5 mA cm −2 current density), respectively, which are much higher than recently reported carbon‐based electrode materials. The superior capacitance and high flexibility of fibrous carbon cloth endow the material great potential for light‐weight energy storage applications. Abstract : Cotton is one of the most abundant biomaterials on earth and is commonly used in our daily lives. The key motivation of this research is to add value to cotton by a single‐step carbonization and simultaneous growth of carbon nanotubes on the carbonized cotton, for flexible and lightweight energy storage.